Finding Security in Fundamental Freedoms - Smith, Margaret Chase, 1897-1995 (Tufts Archival Research Center, 2006)
Margaret Chase Smith, U.S. Senator (Maine), describes the beliefs which make the discouragment of political work worthwhile: a belief in an individual's God-given purpose and rights, such as the right to consideration and courtesy from others, the right to criticize constructively, the right honestly to hold unpopular beliefs, the right to protest orderly, and the right of independent thought. Audio also contains advertisement for "This I Believe" book.